Protection of privacy in the period of Covid-19 pandemic - Toptchiyska, Denitza (Law Journal of New Bulgarian University, 2021)
During the pandemic of COVID-19 in April 2020 the Ministry of Health in Bulgaria began the administration of the Virusafe contact tracking application. With the Law on Emergency Measures and Actions, declared by a decision of the National Assembly of 13th March 2020 amendments to the Electronic Communications Act were adopted. The purpose of the legislative amendments was to provide access of the competent authorities to the localization data from the public electronic communication networks of the individuals, who have refused or do not fulfill the obligatory isolation or treatment under art. 61 of the Health Act. This publication aims to analyze the main features of mobile applications for tracking the contacts of infected persons, as well as the adopted legislative changes, comparing them with the standards of personal data protection provided in the EU General Data Protection Regulation 2016/679 and Directive 2002/58/EC on the right to privacy and electronic communications.